Impact of Flexible Service Delivery on IT Service Providers in the Industry 4.0 Era - Mike Kiersey; Tariq Abdullah; Nauman Moazam Ali (International Journal of Management and Data Analytics)
The digital revolution is a period, where technology and innovation are changing how organizations conduct business and how consumers engage and consume their products and services. This presents both enormous business opportunities and challenges for businesses to adopt new methods of working and the development and advertisement of products. This study aims to investigate the current developments by considering current market trends, technology, business requirements, and strategic approach to provide a digital transformation that impacts services provider’s overall business functionality with the aim of enabling organizations to become more adaptive, responsive, and agile in their IT infrastructure, processes and culture. Our research indicates that digital transformation can be segregated into two key groups of technology and analytics in response to internal and external environments. The technology group is fueling the ability to bring flexible strategic change, by offering organizations significant opportunities to grow and transform their processes. The analytics group brings insights that are required to help transform businesses into becoming more adaptive and responsive to their respective environment. It is concluded that the digital revolution provides a significant opportunity for engaging and supporting business from an IT services provider's perspective. They must adapt to the requirements of their stakeholder and follow a collaborative approach, as no single player will be able to deliver all the business and IT change. They also need to adopt a systematic and flexible strategic approach to exploit the short-term and long-term benefits that digital transformations offer. At the same time, they need to sustain their ability to remain agile and quickly react to new technological trends